Escolarização e Educação Física : aproximações a província do Espírito Santo - Santos, Karen Calegari (2008)
To understand the process of schooling of the Physical Education it was necessary to take a glance back to the century XIX and identify in the official speech the possibility conditions that allowed the Physical Education to be engendered at school as a discipline. For so much, all the information regarding the provincial education was mapped and classified, and some studies concerning the theme that involves both the history of the Education and the history of the Physical Education were mobilized, so that it was possible to establish a dialogue between them, and give visibility of how the organizational procedures of the public instruction took place in Brazil and in the state of Espírito Santo. This way, indications were uncovered about the presence of Physical Education in the culture of the century XIX and at school, in which it was being invented through the body care, public and private hygiene, and the norms of conduct inside schools and in the social spaces.